2013
DOI: 10.1590/s0103-21002013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da educação em saúde no tratamento não medicamentoso da hipertensão arterial

Abstract: Objective: To verify the efficacy of health education on the adherence to non-pharmacological treatment in arterial hypertension. Methods: Habits related to nutrition, physical activity and use of tobacco and alcohol were analyzed, as well as assessment of anthropometric and blood pressure levels, before and after the performance of group health education in 216 hypertensive patients. Results: There was a statistically significant change in the consumption of legumes, in the adherence to physical activity, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
51

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 5 publications
1
10
0
51
Order By: Relevance
“…El número de hipertensos fumadores en la investigación fue de 21 individuos (15,2%) -diferentemente del estudio que presentó porcentaje menor: 7,4% de los pacientes refirieron ser fumadores en la investigación desarrollada en la ciudad de Januária, Minas Gerais, Brasil (3) .…”
Section: Nº 43 Julio 2016unclassified
See 1 more Smart Citation
“…El número de hipertensos fumadores en la investigación fue de 21 individuos (15,2%) -diferentemente del estudio que presentó porcentaje menor: 7,4% de los pacientes refirieron ser fumadores en la investigación desarrollada en la ciudad de Januária, Minas Gerais, Brasil (3) .…”
Section: Nº 43 Julio 2016unclassified
“…Así, son necesarios cambios en algunos hábitos y costumbres, en relación a la alimentación, al consumo de tabaco y de bebidas alcohólicas, así como la práctica de ejercicios físicos. Cambiar el hábito de vida implica cambios en la forma de vivir y en la propia idea de salud que tiene el individuo (2)(3) .…”
Section: Introductionunclassified
“…The socioeconomic characteristics of the study population were similar to those of other samples, where most participants in educational activities provided by Primary Health Care services are female older adults, have low education level and income, and are retired or pensioners 8,19 . In face of the current demographic, epidemiological, and nutritional transitions, and the increase in life expectancy and prevalence of NCD, the health care provided by Primary Health Care needs to be reassessed, prioritizing actions that meet individuals' needs and that help them to adopt healthy habits 23 .…”
Section: Discussionmentioning
confidence: 57%
“…It is consensus that structured health education programs for hypertension patients improve their health conditions, including risk factors and adherence to the recommended treatment 7,18 . Studies that analyzed the effectiveness of educational interventions in hypertension individuals found that education programs improved their behavior and adherence to non-pharmacological treatment considerably 8,19,20 . However, the reluctance of patients and health professionals to believe in the effectiveness of health education actions for a number of reasons is also discussed, such as: the method used, which is often prescriptive, normative, and out of context with respect to the population's reality; the trumping of professional knowledge over popular knowledge and of clinical practice over promotive and preventive actions; the tendency of health actions to be fragmented, disarticulated, and not multidisciplinary; and the population's little interest in changing life habits [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Modificações nos hábitos alimentares se tratam de costumes adquiridos e presentes desde a infância, relacionado à origem étnica e à condição socioeconômica do indivíduo, não se caracterizando, portanto, como hábitos de fácil mudança 17 . Baldissera 18 revela em seus estudos com pacientes hipertensos que os cuidados relacionados à alimentação adequada foi o aspecto mais negligenciado, com apenas 2,78% de adesão.…”
Section: Tem Que Evitar Né?! Se Não Um Dia Ainda Vou Infartar Com Iunclassified